INTERPRETING THE CONCEPT OF THE “AMERICAN DREAM” IN THE WORKS OF THOMAS DREISER. - Fayziyeva Komila Akhrorovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The relevance of this research topic stems from the need for a deeper analysis of the main character of Thomas Dreiser’s novel “An American Tragedy” from the point of view of the destructive influence of capitalist society on his character and fate. This society imposes false life goals and imaginary ideals on people, especially young men and women, and gives priority to material values at the expense of the spiritual component of life. Condemning the external well-being of Americans and their ideals, the American writer critically analyzes such vices as class inequality and corruption inherent in modern reality, which makes his works very relevant.